2014
DOI: 10.1111/gwat.12177
|View full text |Cite
|
Sign up to set email alerts
|

Discrete‐Storm Water‐Table Fluctuation Method to Estimate Episodic Recharge

Abstract: We have developed a method to identify and quantify recharge episodes, along with their associated infiltration-related inputs, by a consistent, systematic procedure. Our algorithm partitions a time series of water levels into discrete recharge episodes and intervals of no episodic recharge. It correlates each recharge episode with a specific interval of rainfall, so storm characteristics such as intensity and duration can be associated with the amount of recharge that results. To be useful in humid climates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(146 citation statements)
references
References 27 publications
(45 reference statements)
3
132
1
2
Order By: Relevance
“…Storm event pulses of recharge were expected to be more diffuse in time and depth for wells with thicker unsaturated zones. Storm‐generated water table responses of these wells were generally more subdued and more autocorrelated over longer lengths of time, with lesser representation of high‐frequency components. Four wells in our study area (Wells 3–6) were analysed with the EMR method for water table fluctuations (Nimmo et al, ). We found that these wells had significantly different RPR (Figure b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Storm event pulses of recharge were expected to be more diffuse in time and depth for wells with thicker unsaturated zones. Storm‐generated water table responses of these wells were generally more subdued and more autocorrelated over longer lengths of time, with lesser representation of high‐frequency components. Four wells in our study area (Wells 3–6) were analysed with the EMR method for water table fluctuations (Nimmo et al, ). We found that these wells had significantly different RPR (Figure b).…”
Section: Discussionmentioning
confidence: 99%
“…A continuous approach for analysing water table fluctuations was presented by Crosbie et al (), but we will use an event‐based approach, called the EMR method (Nimmo, Horowitz, & Mitchell, ). The EMR method combines the water table fluctuation approach (Equation ) with a reproducible process to define and separately estimate recharge for individual storm events (https://wwwrcamnl.wr.usgs.gov/uzf/EMR_Method/EMR.method.html).…”
Section: Methodsmentioning
confidence: 99%
“…[76] studied episodic recharge in the Murray Darling basin, later identifying the nature of episodic recharge across the region [26]. Limited studies [26,28] have assessed in situ groundwater data to characterize changes in recharge. This study evaluated groundwater elevations within the arid southwestern United States to understand potential changes in recharge which may have led to decreases in groundwater storage which Castle et al [31] and Konikow [67] identified within the Lower Colorado River basin and Arizona, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nimmo et al [28] extend the MRC approach to account for episodic recharge events. In that study, selected episodic recharge events from wells were used to estimate recharge.…”
Section: Estimation Of Rechargementioning
confidence: 99%
See 1 more Smart Citation